ANALISIS PENANGANAN GUEST COMPLAIN DALAM MENINGKATKAN KUALITAS PELAYANAN FRONT DESK HARRIS HOTEL BATAM CENTER - Lagarense, Bet El Silisna; Angsana, Jesel Erlangga B; Warroka, Margaretha N; Bawole, Merryany Theovanny; Towoliu, Benny I (PolimdoSains, 2025)
his study aims to analyze the impact of front office service quality on customer satisfaction in handling guest complaints at HARRIS Hotel Batam Center. The research method used is a qualitative approach, gathering data through observations made during an internship at HARRIS Hotel Batam Center. Data collection is conducted using a combination of documentation through reviews to determine the volume of complaints about the hotel and assess how front office service quality impacts customer satisfaction. The results show that front office service quality has a significant effect on customer satisfaction. This finding suggests that improving service quality in the front office can enhance customer satisfaction, which in turn can increase customer loyalty and benefit the hotel. This study contributes to hotel management's efforts to improve service quality and customer satisfaction